A phase I, randomized, placebo‐controlled study of molnupiravir in healthy Japanese to support special approval in Japan to treat COVID‐19. Issue 11 (23rd September 2022) - Nakamura, Keisuke; Fujimoto, Katsukuni; Hasegawa, Chihiro; Aoki, Ikuo; Yoshitsugu, Hiroyuki; Ugai, Hiroyuki; Yatsuzuka, Naoyoshi; Tanaka, Yoshiyuki; Furihata, Kenichi; Maas, Brian M.; Wickremasingha, Prachi K.; Duncan, Kelly E.; et al.
Abstract: Molnupiravir (MK‐4482) is an oral prodrug of the antiviral ribonucleoside analog, N ‐hydroxycytidine (NHC), which has activity against RNA viruses, including severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). We conducted a phase I safety and pharmacokinetic study of molnupiravir in healthy Japanese adult participants. A sample size larger than typically used in pharmacokinetic studies was implemented to collect additional safety data in the Japanese population to support special approval for emergency use in Japan. Single doses of molnupiravir up to 1600 mg and multiple doses of 400 and 800 mg administered every 12 h (q12h) for 5.5 days were generally well‐tolerated. NHC appeared rapidly in plasma and reached maximum concentration ( C max ), with a median time to C max ( T max ) between 1.00 and 2.00 h. Area under the concentration versus time curve from zero to infinity (AUC0–inf ), area under the concentration versus time curve from zero to 12 h (AUC0–12 ), and C max of plasma NHC increased approximately dose proportionally. With q12h dosing, the geometric mean (GM) accumulation ratios for NHC AUC0–12 and C max were ~1 for 400 and 800 mg. Pharmacokinetics of NHC triphosphate (NHC‐TP), the active metabolite of NHC was assessed in peripheral blood mononuclear cells and also demonstrated roughly dose proportional pharmacokinetics. The GM accumulation ratios for NHC‐TP AUC0–12 and C max were ~2.5 for 400 and 800 mg. Following administration with food, only a modest reduction (24%) in plasma NHC C max with comparable AUC0–inf was seen, supporting administration without regard to food.